Modern trends in medical education: A critical appraisal - Bapat, SK (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i3.2748 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 330-333